Motivation of postgraduate learners in pursuing their doctoral degree through collaborative learning - Zakariah, Zulaika (2018)
Huge investments in both the public and private universities are made mainly to attract learners, yet how do we keep them engaged and retained them. On the other hand, how do these universities motivate their part time postgraduate learners to further continue their education? The implication of these learners’ withdrawals will be costly to the learners’ potential success in their career. It will also have repercussion on the universities’ reputation, operational and manpower costs and the upmost loss of all will be in terms of potential knowledgeable workers to the nation. Therefore, it will be imperative that owners and stakeholders of these universities find ways on how to retain its learners. This study thus, focuses on collaborative learning among part time postgraduate learners who are pursuing their doctoral degree at a private open university in Malaysia. A semi-structured face-to-face interview was used to gain more insight on their experience that have an impact on their motivation to continuously work towards achieving their ambition. The finding indicated that through collaborative learning, it had lead to high level of engagement and motivation among learners. Future study should consider alternative modes of enquires such as employing a cross sectional research design and a nationwide survey covering samples from the whole population of the higher institutions of learning in Malaysia that would be more significant in making generalisation.